Program Pendidikan Perempuan Diruang Publik Organisasi ‘Aisyiyah Jawa - Endin Mujahidin; Hana Tazkiyatunnisak (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Women are part of society, women are mothers, brothers, sisters, children, and wives. Providing access to opportunities for women to obtain educational rights by providing several perspectives on women's education thinking, they are tasked with dividing public tasks according to their relevant environment and psychological and physical abilities. The 'Aisyiyah organization is one of the women's empowerment organizations that has a Human Resource management system. The education program for the role of Muslim women in the public sphere in the 'Aisyiyah Organization, namely: Aisyiyah developed various economic empowerment charities in the form of cooperatives (including savings and loan cooperatives), Baitul Mal wa Tamwil, shops/kiosks, Aisyiyah Family Economic Development (BUEKA), home industry, skills courses and social gathering in economics. The women's education program in the political field within the 'Aisyiyah Organization is taken from the field of women's empowerment which is broadly divided into several forms, namely, coaching, training, studies, workshops, seminars, and campaigns. The 'Aisyiyah organization in the social field has a program consisting of: (1) Development of the Sakinah Family, (2) Qoriyah thoyyibah, (3) Guidance for Muallaf and Dhuafa, (4) Social Welfare, (5) Establishing a Health Agency, (6) Housing Stopover for Street Children, (7) Orphanage, (8) Social Compensation Fund, (9) Body Care Team and (10) Posyandu. In advancing education, especially formal education, the 'Aisyiyah Organization has developed education from kindergarten to high school/high school and even college. Keywords: Education, Women, ‘Aisyiyah